Femtosecond visible transient absorption spectroscopy ofChlorophyll f-containing Photosystem I - Kaucikas,M; Nurnberg,D; Dorhliac,G; Rutherford,A; van,Thor J (Biophysical Journal, 2017)
Photosystem I (PSI) from Chroococcidiopsis thermalis PCC 7203 grown under far-red light (FRL; >725 nm) contains both chlorophyll a and a small proportion of chlorophyll f. Here, we investigated excitation energy transfer and charge separation using this FRL-grown form of PSI (FRL-PSI). We compared femtosecond transient visible absorption changes of normal, white-light (WL)-grown PSI (WL-PSI) with those of FRL-PSI using excitation at 670 nm, 700 nm, and (in the case of FRL-PSI) 740 nm. The possibility that chlorophyll f participates in energy transfer or charge separation is discussed on the basis of spectral assignments. With selective pumping of chlorophyll f at 740 nm, we observe a final ∼150 ps decay assigned to trapping by charge separation, and the amplitude of the resulting P700+•A1−• charge-separated state indicates that the yield is directly comparable to that of WL-PSI. The kinetics shows a rapid 2 ps time constant for almost complete transfer to chlorophyll f if chlorophyll a is pumped with a wavelength of 670 nm or 700 nm. Although the physical role of chlorophyll f is best supported as a low-energy radiative trap, the physical location should be close to or potentially within the charge-separating pigments to allow efficient transfer for charge separation on the 150 ps timescale. Target models can be developed that include a branching in the formation of the charge separation for either WL-PSI or FRL-PSI.